Conhecimentos Contemporâneos Ligados Nas Ciências Agrárias vol.1 2021
DOI: 10.35587/brj.ed.0000964
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Use of Chia Mucilage (Salvia Hispanica L.) in the Reduction of Fat in Cookies.

Abstract: O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…Our results are in accordance with those stated by Mohammed, et al (2019) who found that chia seeds meal is a good source of protein, dietary fibers, and polyphenols and they encouraged using it as a functional ingredient to prepare food products. Moreover, the obtained data are in line with those presented by Rocha, et al (2020) who reported that chia mucilage showed high efficiency of water-holding capacity and emulsifying activity when used as a fat replacer to prepare the cookies.…”
Section: Functional Properties Of Pudding Powdersupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are in accordance with those stated by Mohammed, et al (2019) who found that chia seeds meal is a good source of protein, dietary fibers, and polyphenols and they encouraged using it as a functional ingredient to prepare food products. Moreover, the obtained data are in line with those presented by Rocha, et al (2020) who reported that chia mucilage showed high efficiency of water-holding capacity and emulsifying activity when used as a fat replacer to prepare the cookies.…”
Section: Functional Properties Of Pudding Powdersupporting
confidence: 90%
“…This attribute showed that chia seeds flour can bond hydrophilic and hydrophobic components in food materials. The obtained data are similar to that mentioned by Rocha, et al (2020) who found that chia mucilage showed high values of water-holding capacity and emulsifying activity when used as a fat replacer to prepare the cookies.…”
Section: Functional Properties Of Pudding Powdersupporting
confidence: 89%